Pengaruh Daya Tarik Iklan Televisi Cosmetik Wardah Terhadap Keputusan Pembelian - Ilona V. Oisina Situmeang (Jurnal Komunikasi Pembangunan, 2013)
ABSTRACT Television is a media to advertise both products and services, through the advertising it is expected that the audience will be informed about the advertised product or service. To appeal the audiences, an advertisement needs to have certain persuasive input to audiences’ buying decision. There are several dimensions of advertisement magnetism including music (or commonly known as jingle), storyboard, copy or script, endorser, signature slogan, strapline or logo. As for the buying decision, the stages involved in are: problem recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. Research carried out by using a quantitative approach, the explanatory research in nature and survey research methods. The study population is guests of Muslimah Cibubur salon and Sari Tebet salon, amounting to 238 visitors in a week. Research samples are 112 visitors where visitors using Wardah Cosmetic. Pretest trials were conducted on 30 samples obtained for test validity. All statements were declared valid because the result is above 0,361 and reliability tests revealed reliable because the Cronbach’s alpha values ​​were above 0.60. The correlation test obtained results of 0.607 which implies a strong correlation between advertising appeal with the purchasing decision. From linear regression test, result showed that R-square value was 0755, which means that Wardah Cosmetic television advertising has influential value to purchasing decisions as much as 75.5%. From the results of hypothesis testing known that t value was equal to 19,031 and the significance value was 0.00 or less than 0.05 (0.00 <0.05). In conclusion, there is certainly a significant influence of Wardah Cosmetic television advertising to the purchasing decision.